ANALISIS KECURANGAN LAPORAN KEUANGAN MELALUI FRAUD HEXAGON THEORY - Kusumosari, Larassanti; Solikhah, Badingatus (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Financial statements are statements made by company to convey the financial condition,performance, and company’s operational activities aimed at the users of financialstatements as decision-making. The purpose of this study is to analyze fraudulentfinancial statements through fraud hexagon theory, that measured with financial targets,CEO education, political connections, state-owned enterprises, ineffective monitoring,rationalization and CEO duality. The samples of this study consist of 106 companieslisted on the Indonesia Stock Exchange (IDX) in 2014-2018. This study uses data panelregression analysis technique with EViews10. The results of this study show thatfinancial targets, state-owned enterprises, ineffective monitoring, political connections,rationalization, and CEO duality have a significant effect. Meanwhile, CEO educationhave no effect on fraudulent financial statements. Based on this study, the companiesshould report financial statements that describe the real conditions. Further research isrecommended to add other proxies to measure the elements in fraud hexagon theory